2014
DOI: 10.1016/j.comgeo.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

4-Holes in point sets

Abstract: We consider a variant of a question of Erdos on the number of empty k-gons (k-holes) in a set of n points in the plane, where we allow the k-gons to be non-convex. We show bounds and structural results on maximizing and minimizing the number of general 4-holes, and maximizing the number of non-convex 4-holes. In particular, we show that for n >= 9, the maximum number of general 4-holes is ((pi)(4)); the minimum number of general 4-holes is at least 5/2 n(2) - circle minus(n); and the maximum number of non-conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…Similar results for 4-holes can be found in [5]. For 4-gons there is a one-to-one relation to the rectilinear crossing number of the complete graph, and thus results can be found in the respective literature (e.g.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar results for 4-holes can be found in [5]. For 4-gons there is a one-to-one relation to the rectilinear crossing number of the complete graph, and thus results can be found in the respective literature (e.g.…”
Section: Introductionsupporting
confidence: 61%
“…In a forthcoming paper (by Aichholzer, Fabila-Monroy, Hackl, Huemer, Pilz, and Vogtenhuber) this bound is further improved to h 5 …”
Section: Remark (Added During Revision)mentioning
confidence: 85%
“…In [1] it was shown that every set of n points in general position in the plane determines at least 5n 2 2 − Θ(n) empty four-gons and a point set with only O(n 5/2 log n) empty four-gons is given. Our result improves the latter bound to O(n 2 log n).…”
Section: Introductionmentioning
confidence: 99%
“…Research mainly focussed on empty convex polygons. Only recently the number of convex and non-convex polygons in point sets has been studied [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Research mainly focussed on empty convex polygons. Only recently the number of convex and non-covex polygons in point sets has been studied [1,3,4]. In [1] it is shown that every set of n points in general position in the plane determines at least 5n 2 2 − Θ(n) empty four-gons and a point set with only O(n 5/2 log n) empty four-gons is given.…”
Section: Theorem 01 E [N 4 ] = θ(N 2 Log N)mentioning
confidence: 99%